UTILIZING LOGISTIC REGRESSION TO IDENTIFY HOUSEHOLD POVERTY STATUS IN BENUE STATE OF NIGERIA (FUDMA JOURNAL OF SCIENCES, 2024)
Despite numerous poverty alleviation programmes in Nigeria, household poverty continues to rise. This paper aimed to improve poverty detection by analyzing household socio-economic and environmental data using logistic regression models. Data was collected through Google forms and pre-processing and feature extractions were performed. Five logistic models were developed to represent different types of poverty. The models were evaluated for accuracy, precision, recall, and F1 score, achieving 80% for Absolute Poverty and 100% for Chronic/Structural, Conjectural/Transitory, and Locational/Spatial poverty. The analysis revealed that over half of the households were poor, with Spatial/Locational poverty being the most prevalent. Targeting this type of poverty is recommended for effective intervention.
Keywords: Detection; Poverty Status; Logistic Regression; Household; Algorithm